The impact of destructive parental relationships on children's mental health - Campos, Floyd Siqueira (Seven Editora, 2023)
This literature review seeks to understand destructive parental relationships, contextualizing these relationships, not forgetting the concepts necessary to understand the topic, such as the classification of different types of abuse. The effects of destructive relationships and intrafamily abuse on the children's mental health and, finally, the short and long-term psychological consequences for victims of intrafamily abuse and the negative impacts that may arise in the future relationships of these children, who are adults, were also investigated. as children who grow up in environments of destructive parental relationships are more likely to develop emotional disorders, compromising their mental health and judgment to interrupt the cycle of violence. For the work to reach its objective, it was necessary to use books, articles, monographs, dissertations, among others, configuring a bibliographic research, which allowed the understanding of how harmful the abuses of destructive parental relationships are in the mental health of individuals and the need awareness of the signs of intrafamily abuse and measures that can be taken so that it does not happen or is repeated in future generations. DOI:https://doi.org/10.56238/innovhealthknow-023